AIM™ platform: A new immunotherapy approach for viral diseases - Langan, David; Wang, Ruipeng; Tidwell, Keshanti; Mitiku, Selome; Farrell, Alison; Johnson, Catrina; Parks, Adam; Suarez, Lauren; Jain, Shweta; Kim, Sojung; Jones, Kristi; Oelke, Mathias; et al. (Frontiers in Medicine, 2022)
In addition to complications of acute diseases, chronic viral infections are linked to both malignancies and autoimmune disorders. Lack of adequate treatment options for Epstein-Barr virus (EBV), Human T-lymphotropic virus type 1 (HTLV-1), and human papillomavirus (HPV) remains. The NexImmune Artificial Immune Modulation (AIM) nanoparticle platform can be used to direct T cell responses by mimicking the dendritic cell function. In one application, AIM nanoparticles are used ex vivo to enrich and expand (E+E) rare populations of multi-antigen-specific CD8+ T cells for use of these cells as an AIM adoptive cell therapy. This study has demonstrated using E+E CD8+ T cells, the functional relevance of targeting EBV, HTLV-1, and HPV. Expanded T cells consist primarily of effector memory, central memory, and self-renewing stem-like memory T cells directed at selected viral antigen peptides presented by the AIM nanoparticle. T cells expanded against either EBV- or HPV-antigens were highly polyfunctional and displayed substantial in vitro cytotoxic activity against cell lines expressing the respective antigens. Our initial work was in the context of exploring T cells expanded from healthy donors and restricted to human leukocyte antigen (HLA)-A*02:01 serotype. AIM Adoptive Cell Therapies (ACT) are also being developed for other HLA class I serotypes. AIM adoptive cell therapies of autologous or allogeneic T cells specific to antigens associated with acute myeloid leukemia and multiple myeloma are currently in the clinic. The utility and flexibility of the AIM nanoparticle platform will be expanded as we advance the second application, an AIM injectable off-the-shelf nanoparticle, which targets multiple antigen-specific T cell populations to either activate, tolerize, or destroy these targeted CD8+ T cells directly in vivo, leaving non-target cells alone. The AIM injectable platform offers the potential to develop new multi-antigen specific therapies for treating infectious diseases, cancer, and autoimmune diseases.